If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b/6-3=4
We move all terms to the left:
b/6-3-(4)=0
We add all the numbers together, and all the variables
b/6-7=0
We multiply all the terms by the denominator
b-7*6=0
We add all the numbers together, and all the variables
b-42=0
We move all terms containing b to the left, all other terms to the right
b=42
| 4x=18=2x+34 | | 130x+1300=110x | | 3=g−56 | | 2x+6=2(x-3)3 | | 4x+7-9x=25-5x | | b+36=7b | | 2(x-4)5=-x+4 | | n9=6 | | f+9=35 | | 4x-3-14=-1 | | c+5=63 | | 3(x+4)+4x=-37 | | f6=6 | | x+36=38 | | 6x+2x+30=110 | | d−21=69 | | -34=-2y+4(y-5) | | –19f=11−18f | | b/23-5=13 | | j+14=32 | | c+42=50 | | 4q^2=64 | | 6+17b=14+16b | | 3z-32=z | | 18=10-2w | | 5.12p+7.1=-2.2 | | c+64=225 | | 4q^2-64=0 | | 7h=–19+6h | | 3u-39=u+1 | | 11w=-16=7w | | 3x-14x=-55 |